Three-dimensional supernova explosion simulations of 9-, 10-, 11-, 12-, and 13-M⊙ stars. Issue 3 (25th February 2019) - Burrows, Adam; Radice, David; Vartanyan, David
Abstract: Using the new state-of-the-art core-collapse supernova (CCSN) codefornax, we have simulated the three-dimensional dynamical evolution of the cores of 9-, 10-, 11-, 12-, and 13-M⊙ stars from the onset of collapse. Stars from 8 to 13 M⊙ constitute roughly 50 per cent of all massive stars, so the explosive potential for this mass range is important to the overall theory of CCSNe. We find that the 9-, 10-, 11-, and 12-M⊙ models explode in 3D easily, but that the 13-M⊙ model does not. From these findings, and the fact that slightly more massive progenitors seem to explode, we suggest that there is a gap in explodability near 12 to 14 M⊙ for non-rotating progenitor stars. Factors conducive to explosion are turbulence behind the stalled shock, energy transfer due to neutrino–matter absorption and neutrino–matter scattering, many-body corrections to the neutrino–nucleon scattering rate, and the presence of a sharp silicon–oxygen interface in the progenitor. Our 3D exploding models frequently have a dipolar structure, with the two asymmetrical exploding lobes separated by a pinched waist where matter temporarily continues to accrete. This process maintains the driving neutrino luminosity, while partially shunting matter out of the way of the expanding lobes, thereby modestly facilitating explosion. The morphology of all 3D explosions is characterized by multiple bubble structures with a range of low-order harmonic modes. Though much remains to be done in CCSN theory, these and other results in the literature suggest that, at least for these lower mass progenitors, supernova theory is converging on a credible solution.